Lightweight Method for Detecting Fake Authentication Attack on Wi-Fi - Muhammad Yusuf Bambang Setiadji; Ramadhan Ibrahim; Amiruddin Amiruddin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Wireless networks, despite providing better access and flexibility, have vulnerabilities that are easier to realize compared to wired networks. Fake authentication attack can be taken by an attacker prior to carrying out a Man in the Middle attack to intercept the other party's communication. Such an attack is generally carried out in public places that provide free Wi-Fi access. Detection of fake authentication is necessary to maintain communication success. Several methods have been applied to detect fake authentication such as the use of Wireless Intrusion Detection System (WIDS) or certificates on Transport Layer Security (TLS). However, attackers can trick the use of WIDS or TLS. Moreover, the WIDS and TLS techniques require large costs and computations. In this study, a lightweight method based on the comparison of BSSID/MAC address for detecting fake authentication is proposed. The lightweight method is implemented by creating an application that runs on Android mobile phones, and Linux operating system. We compared the detection performance of the device with the proposed application and the one without the proposed application. It can be concluded that the proposed method using comparison of BSSID / MAC address is an effective way to detect fake authentication attacks on Wi-Fi networks.